FEASIBILITY STUDY FOR THE APPLICABILITY OF APPLYING THE HOT RECYCLING TECHNOLOGY FOR REPAIR OF ASPHALT CONCRETE PAVEMENTS (World Science, 2020)
The main technological solutions for the current repair of non-rigid pavement in Ukraine are identified. The cost assessment of repair technologies was carried out depending on the cost of arrangement of the pavement and its maintenance. The technical and economic comparison of traditional technologies of current repair of asphalt concrete pavement and technologies of hot regeneration of asphalt concrete is carried out. An expert method and a method of comparison were used in the research. To calculate the comparative economic efficiency, the indicator of reduced costs was taken into account with the risk-free discount rate. Estimate calculations were performed using the software CMETA_8_Online. Based on the analysis of the obtained results, it is established when comparing only the cost of repairs, the most cost-effective methods of renovating the riding qualities of roads are surface treatment and hot recycling technology by the Reshape method. Technologies of hot regeneration of asphalt concrete and arrangement of wear layers from cast emulsion and mineral mixes are cost-effective when carrying out the comparison for interrepair (5 years for current average repair) period.